Climate Change, Sea Level Rise, and Coastal Disasters. A Review of Modeling Practices - Francesco Bosello; Enrica De Cian (Fondazione Eni Enrico Mattei (FEEM), 2013)
The climate change impacts on sea level rise and coastal disasters, and the possible adaptation responses have been studied using very different approaches, such as very detailed site-specific engineering studies and global macroeconomic assessments of costal zones vulnerability. This paper reviews the methodologies and the modeling practices used by the sea level rise literature. It points at the strengths and weaknesses of each approach, motivating differences in results and in policy implications. Based on the studies surveyed, this paper also identifies potential directions for future research.
Keywords: Q5; Q54; 330; Climate Change Impacts; Adaptation; Sea Level Rise